Effect of peak ground velocity on deformation demands for SDOF systems. - Akkar, S.
The effect of peak ground velocity (PGV) on single degree of freedom (SDOF) deformation demands and for certain ground motion features is described by using a total of 60 soil site records with source to site distances less than 23 km and moment magnitudes between 5.5 and 7.6. The observations based on these records indicate that PGV correlates well with the earthquake magnitude and provides useful information about the ground motion frequency content and strong motion duration that can play a role on the seismic demand of structures. The statistical results computed from non-linear response history analyses of different hysteretic models highlight that PGV correlates better with the deformation demands with respect to other ground motion intensity measures. The choice of PGV as ground motion intensity decreases the dispersion due to record to record variability of SDOF deformation demands, particularly in the short period range. The central tendencies of deformation demands are sensitive to PGV and they may vary considerably as a function of the hysteretic model and structural period. The results provided in this study suggest a consideration of PGV as a stable candidate for ground motion intensity measure in simplified seismic assessment methods that are used to estimate structural performance for earthquake hazard analysis.
Keywords: Peak ground velocity; Ground motion intensity measures; Ground motion features; SDOF deformation demand; Hysteretic models